COMPLETE SEPARATION OF THE VERTICAL AND HORIZONTAL INDEPENDENT COMPONENTS OF THE FLIGHT IN POLICOPTER UAV NAU PKF "AURORA" AND MATHEMATICAL MODEL OF THIS FLIGHT - Kharchenko, Volodymyr; Nakhaba, Alexandr (Proceedings of National Aviation University (archive), 2017)
Purpose: This article presents a mathematical model and the experimental results of automatic flights of the policopter UAV NAU PKF "Aurora" of oktacopter scheme with additional elektroimpeler engines of horizontal thrust. Methods: UAV NAU PKF "Aurora" is developed for experimental flights in manual, semi-automatic and unmanned modes. The uniqueness and scientific novelty of data of flight testes is in a complete separation and isolation of vertical and horizontal components of the flight, which enables a fundamentally new way of moving of vehicle in the aerial space. This approach gives a ability to obtain all advantages and to eliminate disadvantages of helicopter and airplane in fundamentally new aircraft by structure and by function – namely in the policopter flyer with additional independent engines of the lateral thrust. Results: Obtained a new experimental data that allowed to better understand the nature of the physical forces, providing the flight of the policopter. Discussion: Revised a physical basis of the airscrew (propeller), namely on the example of flight of the policopter proved that most of the thrust of the propeller provided by the mechanical impulse (kinetic energy Ек=mv2/2) by the impulse, that a airscrew receives at his collisions with air molecules,but not by the gradient of air pressure below and above the airscrew. Is put forward a hypothesis of gravitational nature of the flight and introduced the notion of "functional antigravity", that a force completely identical in function and opposite on the direction of the force of gravity (gravity force). Deduced a mathematical formula of "functionally antigravitational" transport, namely:G·M·m/R2 = mI·v2/2 – for the flights of the aircraft with a mass m over universal astronomical body with a mass M, and m·g = mI·v2/2 – for the flights of the aircraft with mass m over a planet Earth.